Demographic and phenotypic effects of human mediated trophic subsidy on a large Australian lizard (Varanus varius): meal ticket or last supper? - Tim S Jessop; Peter Smissen; Franciscus Scheelings; Tim Dempster (PLoS ONE, 2012)
Humans are increasingly subsidizing and altering natural food webs via changes to nutrient cycling and productivity. Where human trophic subsidies are concentrated and persistent within natural environments, their consumption could have complex consequences for wild animals through altering habitat preferences, phenotypes and fitness attributes that influence population dynamics. Human trophic subsidies conceptually create both costs and benefits for animals that receive increased calorific and altered nutritional inputs. Here, we evaluated the effects of a common terrestrial human trophic subsidies, human food refuse, on population and phenotypic (comprising morphological and physiological health indices) parameters of a large predatory lizard (∼2 m length), the lace monitor (Varanus varius), in southern Australia by comparison with individuals not receiving human trophic subsidies. At human trophic subsidies sites, lizards were significantly more abundant and their sex ratio highly male biased compared to control sites in natural forest. Human trophic subsidies recipient lizards were significantly longer, heavier and in much greater body condition. Blood parasites were significantly lower in human trophic subsidies lizards. Collectively, our results imply that human trophic subsidized sites were especially attractive to adult male lace monitors and had large phenotypic effects. However, we cannot rule out that the male-biased aggregations of large monitors at human trophic subsidized sites could lead to reductions in reproductive fitness, through mate competition and offspring survival, and through greater exposure of eggs and juveniles to predation. These possibilities could have negative population consequences. Aggregations of these large predators may also have flow on effects to surrounding food web dynamics through elevated predation levels. Given that flux of energy and nutrients into food webs is central to the regulation of populations and their communities, we advocate further studies of human trophic subsidies be undertaken to evaluate the potentially large ecological implications of this significant human environmental alteration.